FISIKA TENTANG PENGARANGAN TEMPURUNG KELAPA DAN ASAP CAIR - Dewanto Kamas Utomo; Dona Mustika; Lilik Hendrajaya (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
E Coconut is a plant that can be used in all parts of a case on husks, shells, water and meat. One of these is the utilization of briquettes and smoke liquid which is the result of the processing of coconut shells. The processing of briquettes and liquid smoke can be studied in physics that can then be used as teaching materials physics. Methods of analysis and observations regarding the processing of coconut shell is done in PT. Tropica Nuficera Industry Yogyakarta. In this case, it has analyzed some physics concepts in the processing briquettes and liquid smoke. Physics concepts are thermodynamics, heat transfer, force and pressure.Keywords: Coconut shell, briqutetes, liquid smoke, physics.